A Modern Approach to Teaching Russian as a Foreign Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article deals with the current state of science "Methods of teaching Russian as a foreign language". The current socio-political situation has required a change in the paradigm of education associated with a change in the role and place of the student in the educational process. Thanks to these shifted emphasis in the educational process, the student is more actively involved in obtaining and interpreting new knowledge, in correcting, expanding and deepening his knowledge and ideas about the world around him, along with the comprehension of a new language and a new linguistic picture of the world. Changing the linguo-cognitive space of students, their motivations, goals, interests, intentional needs in the process of communicative-cognitive activity - all this refers to those factors that should be reflected in modern textbooks and teaching aids, as well as in a new system for monitoring the formation of skills and skills in standards and tests. One of the main requirements of modern linguodidactics, dictated by the demands of the modern pragmatic-dynamic society, is the ability to use theoretical knowledge in practice, i.e. it is necessary to be in line with the practical orientation from the very beginning of training.